FACTORS CAUSING PROBLEMS IN MURABAHAH FINANCING IN SHARIA COMMERCIAL BANKS - M.Yani, Rona Fatima Agna; Nurul, Nurul Putri Ramadhan; Abdul Rozak, Aqilal Zaky Afiya; Sopian, Muthia Lestari; Sugeng Wijaya, Nabila Maulidia (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
Problematic murabahah financing is the risk of congestion in financing distribution. In addition to paying attention to the eligibility of customers, the distribution of financing must also pay attention to sharia principles and the principle of prudence. This writing aims to find out how the factors that cause problematic murabahah financing in Islamic commercial banks and want to find out how to resolve problematic murabahah financing in Islamic commercial banks. This research uses the library study method, this is done because the library sources are obtained from journals, research reports, accredited articles and other sources. The approach in this study uses descriptive qualitative. in the distribution of sharia commercial bank financing, it is in accordance with what is carried out by sharia banks in general by using the precautionary principle. Factors causing problematic murabahah financing in Islamic commercial banks are risks that are beyond the bank's control, customers misusing funds and customer business skills that are less than optimal. In murabahah financing, the problems are caused by two factors, namely internal and external factors. Problematic murabahah financing at Islamic commercial banks is still in the healthy category. The method of solving troubled murabahah financing in Islamic commercial banks means gradual correspondence and financing restructuring. In the troubled murabahah financing settlement method at Islamic commercial banks, if the customer's installments cannot be resolved by means of restructuring, then the guarantee application is carried out using a voluntary system.